Bioaccumulation of PCB-153 and effects on molecular biomarkers acetylcholinesterase, glutathione-S-transferase and glutathione peroxidase in Mytilus galloprovincialis mussels. (July 2016) - Vidal-Liñán, Leticia; Bellas, Juan; Soriano, José Antonio; Concha-Graña, Estefanía; Muniategui, Soledad; Beiras, Ricardo
Abstract: In this study, PCB-153 bioaccumulation kinetics and concentration-response experiments were performed employing wild Mytilus galloprovincialis mussels. In addition, the activity of three enzymatic biomarkers: glutathione S-transferase (GST), glutathione peroxidase (GPx) and acetylcholinesterase (AChE), were measured in the mussel gills. The experimental data fitted well to an asymptotic accumulation model with a high bioconcentration factor (BCF) of 9324 L kg −1 and a very limited depuration capacity, described by a low excretion rate coefficient ( K d = 0.083 d −1 ). This study reports by first time in mussels significant inhibition of GST activity and significant induction of GPx activity as a result of exposure to dissolved PCB-153. In contrast, AChE activity was unaffected at all concentrations and exposure times tested. The effects on both enzymes are time-dependent, which stresses the difficulties inherent to the use of these biomarkers in chemical pollution monitoring programs. Highlights: The bioconcentration factor (BCF) calculated for PCB-153 was 9324 L kg −1 . Low capacity for elimination of this compound was observed ( K d = 0.083 d −1 ). PCB-153 did not affect the AChE activity in M. galloprovincialis . A toxic effect of PCB-153 was revealed by the inhibition of the GST. An increase oxidative stress was suggested by the induction of GPx at all concentrations depending on exposure time. Abstract : The limited capacity for the biotransformation and elimination of PCB-153 in Mytilus galloprovincialis caused an inhibition of the GST activity and an increased oxidative stress.